Univariate and Multivariate Approaches for Identifying Key Differential Volatile Compounds in Wedelia trilobata Essential Oils from Four Different Locations - Tuan Anuar, Tuan Ashraf Faiz; Ramli, Suria; Laosinwattana, Chamroon; Azizan, Kamalrul Azlan (Makara Journal of Science, 2024)
Geographical location is an important factor affecting the production of the volatile compounds and corresponding bioactivity of essential oil (EO). The aim of this study was to determine whether the bioactivity of Wedelia trilobata EO varies by geographical location and identify the key volatile compounds involved in bioactivity. A total of 95 volatile compounds reported in W. trilobata EOs obtained from Brazil, India, Malaysia and Thailand were retrieved from the literature, and changes and key differential volatile compounds were identified with univariate and multivariate methods. Results showed that the monoterpene hydrocarbon content of α-phellandrene and α-pinene were higher than that of W. trilobata EOs from Brazil, India, and Thailand. The W. trilobata EO from Malaysia contained large amounts of limonene and diterpenes. Regarding sesquiterpene hydrocarbons, W. trilobata EOs from Malaysia and Thailand had high germacrene D content. The W. trilobata EO from Brazil had a large amount of trans-β-guaiene, whereas the W. trilobata EO from India had low amounts of sesquiterpene compounds. Partial least squares–discriminant analysis identified β-caryophyllene, α-humulene, and β-mycrene as key differential volatile compounds for differentiating W. trilobata EOs according to their origins. Overall, the findings revealed significant difference in volatile compound composition, showing that the volatile compounds of W. trilobata EO are affected by geographical location.